Etika Pemerintahan sebagai Katalis Diskresi dalam Penanganan Covid-19 Menurut Undang-Undang No. 2 Tahun 2020 - Elya Silvia; Lukmanul Hakim; Rachmat Ramdani (Peneliti.net, 2022)
Implementation of public policy is a very basic demand for modern government. Where every citizen has the right to get good service for goods, services and administrative services provided by the government. The management of relations between the center and the regions has become “fuzzy and unclear”, when Indonesia faces a situation known as a Public Health Emergency. This health emergency arises because of the spread of Corona Virus Disease 2019 (Covid-19) which is spread throughout Indonesia. In addition, when the central government has not determined policies, local governments are required to exercise discretion to decide prevention policies. There are various forms of prevention. There are regions that have taken a policy of closing access in and out of the city for four months, confirming the area as an Extraordinary Event (KLB), and closing flight routes and sea routes. However, this discretionary step that is often taken is sometimes wrong, as if it is not directed. This research uses normative legal research by using literature study. The secondary data collected in this study were re-examined to determine the completeness of the data obtained, their clarity and relevance to the formulation.